Effects of Two Combined Exercise Designs Associated With High-Fat Meal Consumption on Postprandial Lipemia, Insulinemia, and Oxidative Stress. Issue 5 (May 2018) - Farinha, Juliano B.; Macedo, Carlos Ernani O.; Rodrigues-Krause, Josianne; Krüger, Renata L.; Boeno, Francesco P.; Macedo, Rodrigo C.O.; Queiroz, Jéssica N.; Teixeira, Bruno C.; Reischak-Oliveira, Alvaro
Abstract : Abstract: Farinha, JB, Macedo, CEO, Rodrigues-Krause, J, Krüger, RL, Boeno, FP, Macedo, RCO, Queiroz, JN, Teixeira, BC, and Reischak-Oliveira, A. Effects of two combined exercise designs associated with high-fat meal consumption on postprandial lipemia, insulinemia, and oxidative stress. J Strength Cond Res 32(5): 1422–1430, 2018—Impaired postprandial lipemia (PPL) response after the consumption of a high-fat meal (HFM) is linked to diabetes, oxidative stress, and cardiovascular events. The aim of this study was to investigate lipid and glucose metabolism and oxidative stress responses of 2 different combined exercise designs associated with HFM consumption. Eleven healthy and physically active men (27.36 ± 5.04 years) participated in this study. After the pretrial visits, participants were randomly assigned to perform 2-day trials in 3 different conditions (interspaced by at least 1 week): resting (REST), circuit combined exercise (CIRC), or traditional combined exercise (COMB), on the evening of day 1. On the morning of day 2, an HFM was provided and blood samples were obtained before and after 1, 3, and 5 hours of HFM consumption. No differences were found with respect to glucose, thiobarbituric acid–reactive substances, or total thiol levels in between time points or conditions. One-way analysis of variance demonstrated a difference between REST and CIRC ( p = 0.029; reduction of 35.29%) and between REST and COMB ( p = 0.041; reduction of 33.41%) conditions with incremental area under the curve (iAUC) for triacylglycerol levels. A difference between REST and CIRC ( p = 0.03; reduction of 34.22%) conditions in terms of iAUC for insulin was also found. Both CIRC and COMB exercise designs can reduce PPL associated with HFM consumption. Moreover, CIRC reduces the iAUC for insulin, suggesting additional benefits for prescribing this type of exercise.